By-products link crop and livestock production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
In much of the developing world animals and crops are raised through separate enterprises and often seem to compete for the same limited resource, namely land. The problem has recently been aggravated as growing human populations cultivate more land...